2019
DOI: 10.3390/bs9020019
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye Tracking to Explore Facebook Use and Associations with Facebook Addiction, Mental Well-being, and Personality

Abstract: Social networking sites (SNSs) have become ubiquitous in our everyday lives, and for all its communicative benefits, excessive SNS use has been associated with a range of negative health implications. In the present study, the authors use eye-tracking methodology to explore the relationship between individual differences in personality, mental well-being, SNS usage, and the focus of Facebook users’ visual attention. Participants (n = 69, mean age = 23.09, SD = 7.54) completed questionnaire measures for persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 69 publications
0
20
1
1
Order By: Relevance
“…The bulk of the most recent psychological research on wellbeing in social media has been quantitative and used one or more scales via online questionnaires, which means that they are mostly transitional studies, in terms of Gosling and Mason (2015). Nonetheless, these studies present specific features of the other two types of studies, like considering the role of social media in generating and disseminating certain phenomena (e.g., addiction) or offering new perspectives, like an eye-tracking methodology (Hussain et al, 2019). Atroszko et al (2018) used one scale to study the relationship between Facebook addiction and psychosocial functioning and different dimensions of well-being in undergraduate students in Poland through the validation of the Bergen Facebook Addiction Scale (BFAS).…”
Section: Well-being Research Through the Collection Of Social Media Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the most recent psychological research on wellbeing in social media has been quantitative and used one or more scales via online questionnaires, which means that they are mostly transitional studies, in terms of Gosling and Mason (2015). Nonetheless, these studies present specific features of the other two types of studies, like considering the role of social media in generating and disseminating certain phenomena (e.g., addiction) or offering new perspectives, like an eye-tracking methodology (Hussain et al, 2019). Atroszko et al (2018) used one scale to study the relationship between Facebook addiction and psychosocial functioning and different dimensions of well-being in undergraduate students in Poland through the validation of the Bergen Facebook Addiction Scale (BFAS).…”
Section: Well-being Research Through the Collection Of Social Media Datamentioning
confidence: 99%
“…The findings of this study indicate that Facebook as an essential element that can improve the psychological well-being and socialization of the homeless (Calvo and Carbonell, 2018). Hussain et al (2019) used four questionnaires and an eyetracking methodology to study social networking site (Facebook) use and its relation to different indicators of well-being (mental well-being, depression, anxiety, stress, and self-esteem). The study of the interactions with the areas of interest of the interface of this social network found that Facebook addiction, personality variables, and the Facebook features that individuals interact with are determinant in the individual outcomes related to wellbeing variables.…”
Section: Well-being Research Through the Collection Of Social Media Datamentioning
confidence: 99%
“…The appropriate rate for users to access online social networks is a theme that has been widely discussed in the sphere of Psychology [3], [20], [21], [31], [32]. According to Sean Parker, founder of Napster and former president of Facebook, Facebook is a system designed to exploit human vulnerability [35].…”
Section: A Psychology and Addictionmentioning
confidence: 99%
“…After algebraic manipulation, and noting that the two summations in (21) have closed expressions, we obtain a simple expression for V (see (12)),…”
Section: B Expression For V Under the Exponential Modelmentioning
confidence: 99%
“…Individuals' evaluation of trust in message source may impact perceptions of credibility in the health message, resulting in acceptance of (mis)information. Common patterns in which individuals interact with their social media have been identified through eye-tracking studies, examining information processing and attention to components of social media messages (Cipresso et al, 2019;Hussain et al, 2019). One study showed users pay attention to the source of a Facebook news post and use this information as a criterion for the decision to read or to skip the post, revealing that users spend more time looking at posts from highly credible sources compared to sources with lower credibility (Sülflow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%